2020
DOI: 10.1097/rlu.0000000000003246
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of a Small Cell Lung Cancer by 18F-Choline PET/CT Performed for Recurrent Hyperparathyroidism After Parathyroidectomy

Abstract: We report the case of a 64-year-old woman with musculoskeletal pain and elevated serum parathyroid hormone who had undergone parathyroidectomy for primary hyperparathyroidism 4 years earlier. An 18F-choline PET/CT scan was performed and incidentally showed an intense uptake in a right upper lobe pulmonary nodule and in the right hilar, mediastinal, and cervical lymph nodes. Histopathological analysis confirmed the diagnosis of a small cell lung cancer. Clinical symptoms and recurrent hyperparathyroidism were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Table 3 shows the significant differences between the subgroups of lesions: adenomas, hyperplasias, and other diagnoses only proven histologically. Differential diagnoses were normal parathyroids, one lymph node metastasis from a small cell lung cancer ( 26 ), and benign lymph nodes. Hyperfunctional glands had a higher SUV max ( p = 0.0085) and a higher liver ratio ( p = 0.0002) than differential diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the significant differences between the subgroups of lesions: adenomas, hyperplasias, and other diagnoses only proven histologically. Differential diagnoses were normal parathyroids, one lymph node metastasis from a small cell lung cancer ( 26 ), and benign lymph nodes. Hyperfunctional glands had a higher SUV max ( p = 0.0085) and a higher liver ratio ( p = 0.0002) than differential diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Serum PTHrP correction upon pancreatic tumor removal might prove a useful prognostic marker in some of these cases [ 172 ]. Exceptionally, persistent hypercalcemia in patients who underwent surgery for primary hyperparathyroidism might not be a recurrent or persistent hyperparathyroidism but hypercalcemia of malignancy [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for lung cancers, it has been demonstrated that the uptake of [ 18 F]fluorocholine is correlated with the proliferation of tumor cells; furthermore, the [ 18 F]fluorocholine uptake mechanism is related to the overexpression of choline kinase and phosphorylcholine-cytidyl transferase in lung tumors [ 6 ]. A previous case reported the incidental detection of SCLC by [ 18 F]fluorocholine PET/CT performed for a non-oncological indication (primary hyperparathyroidism) [ 7 ]. Our case demonstrated that coexisting tumors such as HCC and SCLC showing increased cell membrane turnover can be detected by radiolabeled choline PET/CT.…”
mentioning
confidence: 99%